Rethinking School Health : A Key Component of Education for All - Bundy, Donald (World Bank, 2012)
Education is one of the most important drivers of the development of individuals and societies. It not only has powerful implications for the creation of human capacity, but also helps people realize their full potential and expand their connections with the world. Economic analyses repeatedly demonstrate that education gives a high economic return within the life - span of an individual and is a key factor underlying the economic growth of nations. Viewed from these perspectives, the decision at the turn of the millennium of governments and development partners to pursue the goal of Education for All (EFA) was not only an important contribution to one sector, but the launch of an endeavor with major implications for the future of humanity. The early perception of the goal of EFA was that all children should have access to education-every child should be able to exercise the right to go to school. This limited goal soon broadened to address the quality of the education that a child received at school and the factors that ensured the child was able to stay in school long enough to learn enough. These additional objectives have expanded the goal of EFA, so that it now aims to ensure that every child has the opportunity to complete an education of good quality, although definitions of quality and completeness remain under discussion. The question now is not whether school health and school feeding programs are necessary to EFA, but how they can be implemented at meaningful scale in the poorest countries, which need them the most.